An Investigation into the Efficiency of Utilization of Artificial Game Water Supplies by Wildlife Species in the North Eastern Kalahari Region of Hwange National Park in Zimbabwe - Sungirai, Marvelous; Ngwenya, Mary (Science and Education Publishing, 2016)
An observational study was carried out to determine the efficiency of utilization of artificial game water supplies and the demand for water by wildlife species at selected water points in the North Eastern Kalahari region of Hwange National Park, Zimbabwe. Six water points were randomly selected from the two distinct vegetation types. Data was collected from May to November 2005 and this included borehole yield, evaporation and seepage rates as well as wildlife water consumption. Analysis of variance was then carried out in a two level nested design to analyse the data using the GENSTAT 7th edition statistical package software. The study showed that they were significant differences (p<0.001) in the borehole yield, evaporation, seepage and the amount of water consumed during different times of the year and at water points within the different vegetation types. The study has shown that the amount of water pumped by a borehole will meet the dry season water requirements of wildlife species early in the dry season but will fail as the dry season progresses. It is recommended that pumping of water begins early in March and that as the dry season progresses there is need to supplement water supply at certain water points.